Pendekatan Arsitek Franky Parulian Simanjuntak pada Pengembangan Simarjarunjung Hound Sky - Nasution, Aulia Muflih; Andrian, Frenky (ALUR :Jurnal Arsitektur, 2024)
Lake Toba is one of the five North Sumatra destinations considered to be Indonesian Super Priority Destinations. Information obtained from the Central Statistics Agency (BPS) of Simalungun Regency indicates that the number of visitors to Lake Toba tourism spots within Simalungun Regency increased by 55% in 2023. Most of these visitors come from the Parapat and Bukit Indah Simarjarunjung regions. As a result of the numerous national and international events held on Lake Toba, such as the International Formula 1 Powerboat Championship event (F1 Powerboat), the number of accommodations will increase to 83 in 2022. As a consequence of this, the Simalungun region of Lake Toba generally has a high number of accommodations that are in high demand. To accommodate tourists, the Toba Caldera region calls for establishing resorts and other tourist accommodations. Qualitative research methodologies are utilised in this research method. To ensure that the design that is implemented incorporates the Neo-Vernacular architecture of the Simalungun Batak culture, the development of Simarjarunjung Hound Sky in the Toba Caldera region can be accomplished through the approach of architect Franky Parulian Simanjuntak. This can be accomplished by incorporating elements of local culture into the design and utilising Neo-Vernacular architecture.